2014
DOI: 10.1073/pnas.1321785111
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular injection of α-synuclein induces CNS α-synuclein pathology and a rapid-onset motor phenotype in transgenic mice

Abstract: It has been hypothesized that α-synuclein (αS) misfolding may begin in peripheral nerves and spread to the central nervous system (CNS), leading to Parkinson disease and related disorders. Although recent data suggest that αS pathology can spread within the mouse brain, there is no direct evidence for spread of disease from a peripheral site. In the present study, we show that hind limb intramuscular (IM) injection of αS can induce pathology in the CNS in the human Ala53Thr (M83) and wild-type (M20) αS transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
343
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(371 citation statements)
references
References 58 publications
22
343
0
2
Order By: Relevance
“…Retrograde transport of ␣S aggregates followed by seeding and further transmission was suggested as the major mechanism involved, as transection of the sciatic nerve prior to i.m. injection of ␣S fibs significantly delayed, but did not completely block, disease induction in this model (40). Herein, we expand these studies of CNS induction of ␣S pathology from peripheral challenges of ␣S fibs and control proteins by comparing the outcomes of tail vein, intraperitoneal (i.p.)…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Retrograde transport of ␣S aggregates followed by seeding and further transmission was suggested as the major mechanism involved, as transection of the sciatic nerve prior to i.m. injection of ␣S fibs significantly delayed, but did not completely block, disease induction in this model (40). Herein, we expand these studies of CNS induction of ␣S pathology from peripheral challenges of ␣S fibs and control proteins by comparing the outcomes of tail vein, intraperitoneal (i.p.)…”
mentioning
confidence: 98%
“…We previously reported that, consistent with a prion-like mechanism, peripheral hind limb intramuscular (i.m.) injection of ␣S fibs leads to the progressive formation of CNS ␣S pathology in both M20 and M83 ␣S Tg mice and to motor impairment in the latter line of mice (40). Retrograde transport of ␣S aggregates followed by seeding and further transmission was suggested as the major mechanism involved, as transection of the sciatic nerve prior to i.m.…”
mentioning
confidence: 99%
“…Moreover, HEK293 cells expressing human mutant P301L tau develop intracellular tau aggregates and co-culture of these cells with hippocampal neurons induced tau pathology in these neurons [93], indicating a possibility transmission of tau pathology from nonneuronal donor to neuronal cell. Interestingly, the infectivity of prions and α-synuclein between distal non-neuronal cells and the brain has also been reported [98][99][100]. It would be interesting to study whether similar infectivity of tau is observed in vivo in transgenic models or AD.…”
Section: Mechanisms Of Tau Release and Spreadingmentioning
confidence: 90%
“…The role of neuron-glia interaction in the etiology of NDDs is an important area of current investigations due to the involvement of naturally unfolded proteins in prion-like transmission of pathology [16][17][18]24]. The results presented here are in agreement with previous observations of aberrant γ-syn accumulation in the optic nerve astrocytes and spheroids which is not accompanied by the formation of inclusion bodies or deposits [10,11] We identified several types of oxi-γ-syn positive astrocytes with different morphology and examined their immunohistochemical phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent results indicate that γ-syn is easily oxidized at Methionine-38 (Met-38) forming oxidized-γ-syn (oxi-γ-syn) and after oxidation it can induce aggregation of α-syn [15]. Moreover, γ-syn can be transmitted between cells [15] and presumably to spread pathology as was shown for α-syn [16][17][18]. These findings raise a possibility that oxidation and/or aggregation of this protein might be involved in the pathogenesis of some NDDs.…”
Section: Introductionmentioning
confidence: 99%